Application of lipidomics to reveal differences of facial skin surface lipids between atopic dermatitis and healthy infants. (16th October 2019) - Wang, Hecong; Cui, Le; Jia, Yan; Gao, Ying; Zhang, Gaolei; He, Congfen
Abstract: Background: The current knowledge about potential risk factors for atopic dermatitis (AD) is primarily based on the structure and function of the stratum corneum, which is characterized by osmotic defects and abnormal antibacterial function. There are no studies on the difference between facial lipids in infants with AD and healthy infants. Aims: We sought to explore significantly different lipid markers for infants with AD presenting with lesions and healthy infants aged 0‐2 years to guide treatment strategies. Methods: Twenty‐eight patient infants with AD and 32 healthy infants were recruited. Each infant received its surface skin lipids (SSL) on the right cheek. The components of skin lipids were measured by ultra‐performance liquid chromatography‐quadrupoletime‐of‐flight mass spectrometry (UPLC‐Q‐TOF‐MS) to explore significantly different lipid markers by analyzing the detection results using orthogonal partial least squares analysis(OPLS‐DA). Results: There were clear distinctions in the components of SSL between the two groups. Twenty‐nine significantly different lipid markers ( P  ≤ .05) were found. Conclusion: This study confirmed that there were significant differences in the components of the SSL between AD infants with lesions and healthy infants, but also found lipid types, lipid contents, and lipid structures as AD‐related risks.